Research on the Development Status and Innovation Path of Tourism Products in Northern Guangxi Under the Integration of Culture and Tourism - Fu, Han (Art & Design Research, 2020)
Under the background of cultural tourism integration, this paper analyzes the shortcomings of current tourism products by investigating the current market situation of tourism products in northern Guangxi. At the same time, based on the local actual situation, this paper discusses the development and innovation path of tourism products from the aspects of local national culture, landscape elements, integration of science and technology, and advantages of local talents, so as to help tourism products to enhance cultural connotation, create features, improve product function and innovation level, and ultimately promote the development of tourism industry in northern Guangxi.